Fly-Ash as Admixture in Manufacturing of Cement - A Case Study - M.J.B, Alam; A.S.M.A, Awal; M.M, Rahman; MJ.B, Alam; M.S, Rahman; B.K, Banik; S, Islam (Malaysian Journal of Science, 2008)
An attempt has been taken to find out the sustainable use of fly ash which was used as an admixture with Shah Special Cement at 5%, 10% and 15% proportion. Laboratory test for the different parameters including the compressive strength, workability, flexural strength, splitting tensile strength of such mixtures were carried out to determine the optimum content. The obtained results show that almost no sacrifice for the strength of cement due to mixture of fly ash with a proportion of 10%. Ten samples for compressive strength for each specified day, tensile strength for each specified day, flexural strength, splitting tensile strength were cast for 5%, 10%, 15% proportion of fly ash. 5%-10% fly ash was successfully blended with ordinary cement and have positive impact on cement manufacturing.